MODELING THE DISPERSION OF NOx AND SO2 EMISSIONS FROM A PROPOSED BIOGAS PRODUCING FACILITY - Abdul-Wahab, Ahmed S.; Ikhile, E.; En, S. C. F.; Elkamel, A.; Ahmadi, L.; Yetilmezsoy, K. (GLOBAL NETWORK ENVIRONMENTAL SCIENCE & TECHNOLOGY, 2016)
This study aims to model the dispersion of two pollutants: nitrogen oxides (NOx) and sulfur dioxide (SO2) from an onsite biogas fueled generator by using CALPUFF modeling system. CALPUFF is a non-steady state puff simulating software that takes into account, meteorological data, terrain data and land use data, to effectively simulate dispersion from a given source. These data are taken from the different governmental and accredited organizations and used in conjunction with CALPUFF. Results showed a wider dispersion of both pollutants in January as supposed to June. This was due to rapid changes of wind's speed and directionin the month of January. It was also discovered that the emission results were well below the point of impregnation (POI) limits set by the Ministry of Environment for its 24 hour, 1 hour and 30 minute averaging time periods of exposure. The findings of this study reveal that the proposed facility's operation is in compliance with the Ontario regulations and that it should be able to operate in accordance with them, in the winter and summer seasons.
Keywords: Biogas; CALPUFF; Dispersion; Modeling; Nitrogen Oxides; Sulfur Dioxide; POWER-PLANT; COMPLEX; EVALUATE; AERMOD; Environmental Sciences & Ecology